Analisis Penyajian Laporan Keuangan Pada Badan Usaha Milik Desa (BUMDes) (Studi Kasus Pada BUMDes Bersama Bangkit Mandiri Sejahtera Kecamatan Nita) - Maria Nona Ivon; Wilhelmina Mitan; Fransiscus De Romario (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze how the presentation of financial statements at Village-Owned Enterprises (BUMDes) Bersama Bangkit Mandiri Sejahtera, Nita District. By analyzing the financial statements made by BUMDes Bersama Bangkit Mandiri Sejahtera, Nita District, and adjusting to the statement of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The research method used in this study is qualitative research with descriptive methods. Data collection is done through interviews, documentation and observation. The results of this study show that in the presentation of financial statements made by BUMDes Bersama Bangkit Mandiri Sejahtera has not fully implemented financial statements in accordance with SAK EMKM due to limited knowledge of BUMDes management and the absence of training from related parties.